Poland 1918 - 1945 : an interpretive and documentary history of the Second Republic - Stachura, Peter D. 1944- (Routledge, 2004)
Peter Stachura sets out to redeem the reputation of the Second Republic of Poland from failure. He shows how the government consolidated the country in the early 1920s, and provides an assessment of the social and economic achievements of the new state in the years before the outbreak of World War II. nightmare.